(untitled) (Al-Academy, 2021)
The Rafidian artist discussed the headdresses of his idols with a varied scholarly momentum, so each idol had its own cover as this door of diversity contributed to the enrichment of Rafidian thought and full knowledge of their ideas and beliefs consistent with their multiple symbolic connections such as architecture, for example. The previous one, if not its entirety.A research such as this (the discursive connections to the head-covers of the deities of the Mesopotamian civilization) aims to clarify the confusion that occurs through four chapters: The first chapter included: the research problem, the importance of research and the need for it, the objectives of the research, the temporal, spatial and objective limits of research, and the definition of terms. As for the second chapter, where the theoretical framework was depicted in three topics, the first section included (the religious method of the Mesopotamian civilization), the second study was concerned with the study of (the rhetorical links to the deities of the Mesopotamian civilization) and the third on (the structural structure of the head covers of the Mesopotamian gods) and included the third chapter where the research procedures The application side according to the descriptive and analytical approach, and the fourth chapter included the following axes: results, conclusion, recommendations, and suggestions.